POSITION OF THE DECREE OF THE PEOPLE'S CONSULTATIVE ASSEMBLY (TAP MPR) IN THE HIERARCHY OF LEGISLATION IN INDONESIA - Akbar, Aryo; Ibnususilo, Efendi; Taufiqurrahman, Faishal (EKSEKUSI, 2024)
The reinsertion of the People's Consultative Assembly Decree (Tap MPR) into the hierarchical system of Indonesian statutory regulations through Law Number 12 of 2011 concerning the Formation of Legislative Regulations, has caused several problems, namely: 1) The position of the MPR Tap in the hierarchy of statutory regulations. Invitation; and 2) Which state institution should be given the authority to test the MPR Decree. The research results show that the position of the MPR Decree in the hierarchy of laws and regulations in Indonesia is in a "grey" position because after the amendment to Article 3 of the 1945 Constitution, the MPR no longer has the authority to form Decrees containing regulations that come into force. Where initially the Decree was a second-degree statutory regulation, but after the amendment to the 1945 Constitution, the Decree could no longer be issued as a statutory regulation. Meanwhile, in terms of the authority to review the MPR Decree, the authority for such review can be given to the Constitutional Court. If this has to be done, it can be done by making changes to the limitative formulation in the 1945 Constitution. This change could be in the form of adding the authority to review the MPR Decree on the 1945 Constitution by the Constitutional Court through legislative interpretation and/or judicial interpretation.Keywords: Hierarchy, Position of Tap MPR, Laws and Regulations.